2020
DOI: 10.1186/s43055-020-00312-0
|View full text |Cite
|
Sign up to set email alerts
|

Lesion load assessment among multiple sclerosis patient using DIR, FLAIR, and T2WI sequences

Abstract: Background Magnetic resonance imaging (MRI) is one of the diagnostic imaging modalities employing in lesion detection in neurological disorders such as multiple sclerosis (MS). Advances in MRI techniques such as double inversion recovery (DIR) made it more sensitive to distinguish lesions in the brain. To investigate the lesion load on different anatomical regions of the brain with MS using DIR, fluid attenuated inversion recovery (FLAIR) and T2-weighted imaging (T2WI) sequences. A total of 97 MS patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Tawfik et al, [14] and Patzig et al, [12] also noted a 3D detection percentage increase of 80% and 140% respectively. A significant positive association between infratentorial lesions and higher EDSS score or clinical disability was noted as Almutairi et al, also observed [15].…”
Section: Discussionmentioning
confidence: 66%
“…Tawfik et al, [14] and Patzig et al, [12] also noted a 3D detection percentage increase of 80% and 140% respectively. A significant positive association between infratentorial lesions and higher EDSS score or clinical disability was noted as Almutairi et al, also observed [15].…”
Section: Discussionmentioning
confidence: 66%
“…The number of lesions in the infratentorial region is an important factor to predict the disease severity and the long-term disability in MS patients. The specific structure of the infratentorial area regarding high density of neural fibers can explain the finding that the correlation between clinical outcomes and MRI findings in the infratentorial region is more strong than other areas of the brain [32].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, measurement of GM volume is a useful method for assessing the overall GM damage and can be estimated through conventional MRI techniques ( 6 ). Another established measurement for prediction of neurological disorders is the lesion load ( 20 ), since it has been proved that both lesion volume and lesion count are strong predictors of disease course and progressive timepoints. Additionally, detection of MS lesion is of paramount importance since the diagnosis of MS is based on the spatial and temporal distribution of focal demyelination lesions ( 21 ).…”
Section: Detection: Segmentation Methodsmentioning
confidence: 99%